Mobile Application for Used Items Marketplace in UNIMAS - Voon, Yu Cheng (Universiti Malaysia Sarawak (UNIMAS), 2019)
This report is about the development of mobile application for used items marketplace in UNIMAS. This application provides a marketplace for users to buy and sell used items simple and fast. To make sure this application protects the users from scammer and deceiver, this application is equipped with administrator moderation to manage all the user account, Ad items and complaints. This application provides consumer to consumer transaction so the transaction process can be done easily and fast. Before the development process of this application is conducted, the existing mobile applications that are related to this application are reviewed to gather the features and functionality that are suitable and practicable. After that, the requirement has been analysed and from the requirement gathered, the system has been designed to make sure the development process is carried out systematically. Then, the implementation and testing of the application has been described in detail. Finally, some future work has been suggested.